Morphological Image Processing Approach of Vehicle Detection for Real-Time Traffic Analysis - Y M, Prutha; S G, Anuradha (International Journal of Computer Sciences and Engineering, 2014)
Along with the economical development, traffic has increased enormously these days. Due to the increasing urban population and hence the number of cars, need of controlling the traffic in streets, highways and roads is vital. In this paper, a system that detects the vehicle in real time in highway is done by using image processing. The implementation includes algorithms used for real time vehicle detection, which is based on background differencing and morphological operations. Another image processing technique used is the edge detection technique where the edges of the object is detected and other techniques for calculating traffic parameters such as counting the number of cars, speed of the cars by applying a threshold value .